Monte Carlo simulation and measurement of nanoscale n-MOSFETs. - Bufler, F.M (IEEE Transactions on electron devices)
The output characteristics of state-of-the-art n-MOSFETs with effective channel lengths of 40 and 60 nm have been measured and compared with full-band Monte Carlo simulations. The device structures are obtained by process simulation based on comprehensive secondary ion mass spectroscopy and capacitance-voltage measurements. Good agreement between the measured output characteristics and the full-band Monte Carlo simulations is found without any fitting of parameters and the on-currents are reproduced within 4%. The analysis of the velocity profiles along the channel confirms that the on-current is determined by the drift velocity in the source side of the channel. Analytic-band Monte Carlo simulations are found to involve an overestimation of the drain current in the nonlinear regime which becomes larger for increasing drain voltage and decreasing gate length. The discrepancy originates from a higher nonlinear drift velocity and a higher overshoot peak in bulk silicon which is due to differences in the band structures above 100 meV. The comparison between analytic-band and full-band Monte Carlo simulation therefore shows that the source-side velocity in the on-state is influenced by nonlinear and quasiballistic transport.